KELAYAKAN BUKU TEKS BAHASA INGGRIS PADA PROGRAM STUDI KEBIDANAN, POLITEKNIK KESEHATAN SE-JAWA TIMUR - Sabekti, C. A.; Setyadi, Dwi; Rahmawati, Rina (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2013)
Orientation: This research is about the development of CTL-based English instructional mate- rials of English for Specific Purpose.Research Purpose: The purpose of this study is to determine the type of contextual materials used in English language, develop English for Specific Purpose materials that integrate CTL, and assess the effectiveness of instruction by using CTL-based materials.Motivation for the study: The research provides a starting point in identificating the students need and provide them with suitable materials in the form of module.Reasearch design, Approach, and Method: The method of research was a research and development. The method of data collection were observation, interviews, study the document, portofolio, and tests. The technique of data analysis in this study used mixed method.Main Findings: The Results showed that ESP materials used POLTEK Jawa Timur looked traditional and they were focused more in using textbook, white board, and face to face interaction. CTL based materials has been developed systematically and revised based on recommendation, and the use of CTL based materials is more effective than ordinary materials.Contribution/Value-add: The process leads the lecturers in collaboratively handling studentsâ difficulties. It also showed the students the proper way of citation, understanding, and synthesizing the terms related to the ideas they had.